GRADUATE STUDENTS’ PERCEPTIONS OF ARTIFICIAL INTELLIGENCE-INTEGRATED SELF-ASSESSMENT PRACTICES IN ARTICLE WRITING - Sari, Intan Fatma; Hidayati, Sari (Academic Journal Perspective: Education, Language, and Literature, 2025)
The study investigates graduate students’ perceptions of Artificial Intelligence-integrated self- assessment in academic writing. Using narrative inquiry, the study investigated how students experience AI in their self-assessment and writing processes. The participants were three Indonesian EFL graduate students who enrolled in a scientific writing course. The data were collected using a questionnaire, semi-structured interviews, and student artifacts. The data analysis technique employed was thematic analysis, which aimed to uncover the main themes in students' experiences. The findings indicate that AI tools supported students’ understanding of writing conventions and increased confidence and motivation to learn more. The students exhibited a transition from relying on AI to a more independent process of selectively using AI feedback with human feedback. Despite the advantages of AI tools, the study also identified challenges using AI, specifically regarding the conceptual aspects of writing, including argumentation and knowledge of a specific discipline. The findings indicate that AI is a practical supplementary tool in academic writing, but human feedback remains essential. The research concludes with suggestions for further research, including the development of AI tools that provide more specific feedback when applying them. When using AI, students may need to establish a system of using human feedback and AI feedback in parallel to cultivate accuracy and critical analysis for academic writing.